Analisis Kesulitan Belajar Pendidikan Agama Islam (PAI) dalam Tinjauan Psikologi Kognitif: Studi Kasus di SDN 07 Lasi Tuo - Latifur Rahmi; Alfi Rahmi (YASIN, 2026)
Learning difficulties in Islamic Religious Education (PAI) among elementary school students have received attention in various studies, but research that specifically analyzes this issue from the perspective of cognitive psychology, particularly regarding encoding processes, schema formation, retrieval, attention, and information processing, remains relatively limited. This study aims to analyze PAI learning difficulties from a cognitive psychology perspective among students at SDN 07 Lasi Tuo. This study used a qualitative approach with a case study design, involving PAI teachers and students experiencing learning difficulties as informants selected through purposive sampling. Data were collected through observation, semi-structured interviews, cognitive diagnostic tests, and documentation, and were then analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. The results show that PAI learning difficulties are influenced by five main factors, namely encoding failure, weak schema connection, retrieval failure, low selective attention during learning, and obstacles in understanding abstract religious concepts. The conclusion of this study affirms that PAI learning difficulties are not only related to pedagogical aspects but are also influenced by students’ cognitive mechanisms in receiving, organizing, storing, and retrieving information. The implications of this study provide theoretical contributions to the development of cognitive psychology studies in Islamic education, as well as practical implications for PAI teachers in designing learning strategies that are more meaningful, effective, and aligned with the cognitive developmental characteristics of elementary school students.